A Quantitative Assessment of the Annual Contribution of Platform Downwearing to Beach Sediment Budget: Happisburgh, England, UK - Andres Payo; Mike Walkden; Michael A. Ellis; Andrew Barkwith; David Favis-Mortlock; Holger Kessler; Benjamin Wood; Helen Burke; Jonathan Lee (Journal of Marine Science and Engineering, 2018)
Field and numerical investigations at Happisburgh, East coast of England, UK, sought to characterize beach thickness and determine geologic framework controls on coastal change. After a major failure of coastal protection infrastructure, removal of about 1 km of coastal defence along the otherwise protected cliffed coastline of Happisburgh triggered a period of rapid erosion over 20 years of ca. 140 m. Previous sensitivity studies suggest that beach thickness plays a major role in coastal recession. These studies were limited, however, by a lack of beach volume data. In this study, we have integrated the insights gained from our understanding of the Quaternary geology of the area, a novel non-intrusive passive seismic survey method, and a 3D novel representation of the subsurface source and transportable material into a coastal modelling environment to explore the role of beach thickness on the back wearing and downwearing of the cliffs and consolidated platform, respectively. Results show that beach thickness is non-homogeneous along the study site: we estimate that the contribution to near-shore sediment budget via platform downwearing is of a similar order of magnitude as sediment lost from the beach and therefore non-negligible. We have provided a range of evidence to support the idea that the Happisburgh beach is a relatively thin layer perched on a sediment rich platform of sand and gravel. This conceptualization differs from previous publications, which assume that the platform was mostly till and fine material. This has direct implication on regional sediment management along this coastline. The present study contributes to our understanding of a poorly known aspect of coastal sediment budgeting and outlines a quantitative approach that allows for simple integration of geological understanding for coastline evolution assessments worldwide.